Chapter 11 Governance of Dual Use Research in the EU The Case of Neuroscience - Ulnicane, Inga (Taylor & Francis, 2020)
This chapter focuses on the governance of dual-use research in neuroscience in the EU. At a time when many countries are making unprecedented investments in the field of neuroscience, which sometimes are described as the 'gold rush' or 'golden age' of neuroscience, the European Commission has been supporting neuroscience - or brain research as it is sometimes called - via its research and innovation FP. In the FP7 that lasted from 2007-2013, the Commission invested €3.1 billion in neuroscience. In the first five years (until November 2018) of the following Horizon 2020 programme, a similar sum of €3.2 billion was invested (European Commission 2019a). This funding supports a number of neuroscience research projects included within the Future and Emerging Technologies (FET) programme.